Impact of Medications for Stable Angina Pectoris on Osteoporosis: A Review of Current Evidence - Wang RA; Xu CX (Journal of Multidisciplinary Healthcare)
Rui-Ang Wang, Chen-Xi Xu School of Medicine, Yangzhou University, Yangzhou, Jiangsu Province, 225001, People’s Republic of ChinaCorrespondence: Chen-Xi Xu, School of Medicine, Yangzhou University, No. 136 of Jiangyang Middle Road, Hanjiang District, Yangzhou, Jiangsu Province, 225001, People’s Republic of China, Tel +86 13625217622, Email xuchenxi_yu@126.comAbstract: Stable angina pectoris (SAP) and osteoporosis (OP) are both prevalent conditions among the elderly population. Compared to SAP, the prevention and management of OP are often neglected. Furthermore, certain medications used long-term for SAP may exert significant effects on bone metabolism. This review summarizes the impact of commonly prescribed SAP medications on OP. Extensive research indicates that nitrates not only promote vascular and osteogenic coupling via the nitric oxide (NO)-cyclic guanosine monophosphate (cGMP)-protein kinase G (PKG) pathway, enhancing the osteogenic effects of estrogen and mechanical stimulation, but also regulate bone immunity through receptor-interacting protein kinase 3 (RIPK3), promoting bone remodeling. β-Blockers promote osteoblast proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) via the cAMP/PKA signaling pathway, stimulating bone formation, while concurrently inhibiting osteoclasts and reducing bone resorption. Statins, which inhibit 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase to regulate lipid metabolism, also upregulate bone morphogenetic protein 2 (BMP-2) expression, inducing osteogenic differentiation of BMSCs, and inhibit osteoclast differentiation and activity, thereby promoting bone formation and suppressing bone resorption. Aspirin (AS) activates osteoblasts and their precursor cells, stimulates angiogenesis, mitigates inflammatory responses, promotes bone regeneration, and accelerates bone repair. However, clopidogrel reduces osteoblast numbers via P2 receptor-mediated extracellular nucleotide signaling and promotes adipogenic differentiation of BMSCs; furthermore, its metabolism can decrease serum 25-hydroxyvitamin D levels, adversely affecting skeletal health. Calcium channel blockers (CCBs) exhibit a largely neutral effect on bone health in clinical evidence, although basic research suggests potential benefits. The heterogeneity in research findings profoundly reflects the complexity of bone metabolism and the limitations of current studies. Synthesizing the evidence, preferential consideration may be given to nitrates, β-blockers, statins, and aspirin for SAP patients with coexisting OP or at significant risk; when clopidogrel is used, enhanced monitoring of bone parameters and intensified prevention and treatment of OP are recommended.Keywords: bone metabolism, bone mineral density, drugs, osteoporosis, stable angina pectoris